Innovative approach for tear trough deformity correction using higher G prime fillers for safe, efficacious, and long‐lasting results: A prospective interventional study. (27th August 2021) - Vadera, Sapna; Shome, Debraj; Kumar, Vaibhav; Doshi, Komal; Kapoor, Rinky
Abstract: Background: One of the most challenging areas for facial rejuvenation is the lower eyelid. Apart from the protruding orbital fat causing lower lid bags, a discrete entity called the "tear trough deformity" is distinguishable in this area. Aim: The objective of this study is to compare and evaluate the standard technique of tear trough deformity correction with the lateral injection technique using a high G prime filler to establish a guideline for the safe and effective correction of tear trough deformity. Methods: A prospective, double‐blind, study was carried out from Dec 2017 to 2019 including 30 participants in the age range of 35–60 years. The participants were divided into two groups of 15 patients each. In group A patients, conventional technique with a low G Prime filler was used, whereas in group B, lateral injection technique with a high G Prime filler was used. Results: Marked improvement was seen in appearance and skin quality on both the sides in all the patients. As compared to our technique (lateral injections) where a mean of 0.5 ml of filler was used to lift the cheek and reduce the tear trough, the standard technique (Mauricio de Maio's 3‐point tear trough reshape technique) required a mean of 1.2 ml of filler for the same. Post‐procedure complications including bruising and Tyndall effect were much higher (statistically significant) using the standard medial technique for the correction tear trough. Conclusion: Aesthetically satisfying results for the tear trough correction are possible, without actually injecting the tear trough directly, based on the knowledge of the underlying anatomy.